Ficus virens proanthocyanidins induced apoptosis in breast cancer cells concomitantly ameliorated 5-fluorouracil induced intestinal mucositis in rats. (December 2017) - Chen, Xiao-Xin; Lam, Kar Ho; Chen, Qing-Xi; Leung, George Pak-Heng; Tang, Sydney Chi Wai; Sze, Stephen Cho-Wing; Xiao, Jian-Bo; Feng, Feng; Wang, Ying; Zhang, Kalin Yan-Bo; Zhang, Zhang-Jin
Abstract: 5-Fluorouracil (5-FU) is a commonly used chemotherapeutic agent for breast cancer. However, its use often leads to drug resistance and mucositis. This study aimed to investigate whether proanthocyanidins from Ficus virens possessed anti-breast cancer and anti-mucositis activities. The results showed that the cytotoxic effects of the proanthocyanidins against MDA-MB-231 and MCF-7 breast cancer cells were in the order of stem barks proanthocyanidins (SPAs) > leaves proanthocyanidins > fruits proanthocyanidins. Moreover, SPAs induced apoptosis in both cell lines which were accompanied with an increase in loss of mitochondrial membrane potential, production of reactive oxygen species, Bax to Bcl-2 protein expression ratio, and activated caspase 3. Furthermore, intraperitoneal injection of 5-FU (150 mg/kg body weight) resulted in body weight loss and jejunal injury in the rats while administration of SPAs (100 mg/kg body weight) counteracted these changes. Collectively, our study demonstrated that SPAs induced apoptosis cell death in breast cancer cells while ameliorating the symptoms of intestinal mucositis in rats.Therefore, SPAs merits further exploration as a potential therapeutic agent for breast cancer and chemotherapy-induced mucositis. Graphical abstract: Highlights: Ficus virens leaves, fruits, and stem bark proanthocyanidins contained propelargonidin, procyanidins, and prodelphinidins. Ficus virens stem bark proanthocyanidins exerted cytotoxic activities against MDA-MB-231 and MCF-7 cells. Ficus virens stem bark proanthocyanidins induced oxidative stress and apoptosis in MDA-MB-231 and MCF-7 cells. Ficus virens stem bark proanthocyanidins ameliorated 5-fluorouracil induced intestinal mucositis in rats.